Finding golden mean in a physics exercise. (28th April 2017) - Benedetto, Elmo
Abstract: The golden mean is an algebraic irrational number that has captured the popular imagination and is discussed in many books. Indeed, some scientists believe that it appears in some patterns in nature, including the spiral arrangement of leaves and other plant parts. Generally, the golden mean is introduced in geometry and the textbooks give the definition showing a graphical method to determine it. In this short note, we want to find this number by studying projectile motion. This could be a way to introduce the golden mean (also said to be the golden ratio, golden section, Fidia constant, divine proportion or extreme and mean ratio) in a physics course.